2007
DOI: 10.1007/s10706-007-9127-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of system variables and particle size on physical characteristics of air sparging plumes

Abstract: Air was injected through a well in a thin transparent tank filled with saturated glass beads to study how the size and air saturation of air sparging plumes are affected by particle size and gradation; operational parameters such as injection pressure, well depth, injection pressure pulsing; and well outlet configuration. V-shaped air plumes with an apex between 408 and 608 were obtained for all tests. The air pressure required to initiate sparging agreed closely with the sum of the air entry pressure and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…This can be explained by the air channel “memory”: during subsequent sparging cycle, trapped air provides less resistance to flow than the original water filled pores. Thus, an initial higher injection pressure lowers the entry pressure in the following cycles (Baker and Benson ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This can be explained by the air channel “memory”: during subsequent sparging cycle, trapped air provides less resistance to flow than the original water filled pores. Thus, an initial higher injection pressure lowers the entry pressure in the following cycles (Baker and Benson ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies pointed out pronounced advantages applying AS in a pulsed operation rather than using it in a continuous operation mode (Shah et al 1995;Johnson et al 1999;Suthersan 1999;Kirtland and Aelion 2000;Heron and Gierke 2002;Yang et al 2005;Baker and Benson 2007;Balcke et al 2009). A field scale study, reported by Heron and Gierke (2002), showed that applying AS in a pulsed mode accelerated the time weighted average mass removal by 40% to 600% (depending on the "aggressiveness" of the pulsing).…”
Section: Effect Of Changes In the Injection Rate On As Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have demonstrated improved air distribution using pulsed (periodic) air injection below (Shah et al, 1995; Johnson et al, 1999; Kirtland and Aelion, 2000; Heron et al, 2002; Yang et al, 2005; Baker and Benson, 2007; Balcke et al, 2009; Ben Neriah and Paster, 2017) and above (Rathfelder et al, 2000) the water table. The positive effects of step‐pulsed or harmonically changing air‐injection rates have been attributed to enhanced air mixing, which in turn increases the contact of the injected fresh air with the volatile contaminants (Ben‐Neriah and Paster, 2016), and to the reduced restrictive effect of preferential flow and fingering on the air's horizontal spread (Thomson and Johnson, 2000).…”
mentioning
confidence: 99%